Identification of the functional initiation codons of a phase-variable gene of Haemophilus influenzae, lic2A, with the potential for differential expression. - Dixon, K; Bayliss, C; Makepeace, K; Moxon, E; Hood, D (2007)
Simple sequence repeats located within reading frames mediate phase-variable ON/OFF switches in gene expression by generating frameshifts. Multiple translation initiation codons in different reading frames are found upstream of most Haemophilus influenzae tetranucleotide repeat tracts, raising the possibility of multiple active reading frames and more than two levels of gene expression for these loci. Phase variation between three levels of gene expression (strong, weak, and none) was observed when lic2A was fused to a lacZ reporter gene. The lic2A 5' CAAT repeat tract is preceded by four 5' ATG codons (x, y, z1, and z2) in two reading frames. Each of these initiation codons was inactivated by site-directed mutagenesis. Strong expression from frame 1 was associated with x but not y. Weak expression from frame 2 was mainly dependent on the z2 codon, and there was no expression from frame 3. Using monoclonal antibodies specific for a digalactoside epitope of lipopolysaccharide whose synthesis requires Lic2A, two levels (strong and undetectable) of antibody reactivity were detected, suggesting that weak expression of lic2A is not discernible at the phenotypic level. Inactivation of the x initiation codon resulted in loss of strong expression of the digalactoside epitope and elevated killing by human serum. The failure to detect more than two phenotypes for lic2A, despite clear evidence of weak expression from the z1/z2 initiation codons, leaves open the question of whether or not multiple initiation codons are associated with more complex patterns of phenotypic variation rather than classical phase-variable switching between two phenotypes.